Glabellar Botulinum Toxin Injection Improves Depression Scores: A Systematic Review and Meta-Analysis. Issue 1 (20th May 2022) - Crowley, Jiwon S.; Silverstein, Max L.; Reghunathan, Meera; Gosman, Amanda A.
Abstract : Background: Depression is a leading cause of disability worldwide. Preliminary evidence suggests that glabellar onabotulinumtoxinA injections improve depression scores with few side effects compared to current first-line antidepressant medications. The authors' review reports on these studies, hypothesizing that glabellar onabotulinumtoxinA injections can be an alternative safe and effective treatment for depression. Methods: A systematic review and meta-analysis of the relevant literature was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The PubMed, Cochrane Library, Embase, and Scopus databases were searched in August of 2020 using the keywords ["botox" OR "botulinum"] AND ["mood" OR "depression"] for articles published between 1980 and 2020. Prospective studies and randomized controlled trials on the use of glabellar onabotulinumtoxinA injections for the primary purpose of treating depression were considered. The primary endpoint for the meta-analysis was the mean difference in primary depression scores after treatment, along with a second endpoint of the standardized mean difference in depression scores among treated patients including all nine studies. Results: Of the 499 reviewed articles, nine studies were included that reported improvement in mean depression scores from baseline. All five randomized controlled trials reported an improvement in mean depression scores at 6 weeks after treatment, with a weighted average change of −8.39 points ( p < 0.0001). The aggregate standardized mean difference from baseline to the primary endpoint across all nine prospective studies was −1.61 SD ( p < 0.0001). Conclusion: Meta-analysis and systematic review of the included studies provide support for an antidepressant effect of glabellar onabotulinumtoxinA injections.